(untitled) (aSSIST Business Review, 2026)
This study applies the SER-M (Subject–Environment–Resource–Mechanism) model to structurally analyze the strategic operation of emotional politics. Using Donald Trump’s 2016 U.S. presidential campaign as a case study, it examines both theoretically and empirically the executional flow that links the repetition of emotional vocabulary, identity formation, restoration of political efficacy, and behavioral change. Findings reveal that emotional vocabulary functions not merely as rhetorical expression but as a strategic resource that reconstructs voter perception and identity. It serves as a core mechanism that fosters political awareness and mobilization. The SER-M model integrates theories of emotional politics, political efficacy, and strategic communication, offering a comprehensive analytical framework for understanding how political strategies are formed and executed within specific structural contexts. This research contributes to a deeper structural understanding of emotional politics by demonstrating that emotional language is not incidental but central to the formation of political subjectivity and collective identity. It also highlights the ethical implications of emotional strategy, emphasizing the need for responsible use of affective language in political discourse. The study concludes by proposing future directions for comparative research and model expansion across diverse political and cultural settings.